Comparative study of three thermosyphon solar water heaters made of flat-plate collectors with different absorber configurations. Issue 5 (28th May 2017) - Koholé, Yemeli Wenceslas; Tchuen, Ghislain
Abstract : The paper presents a comparative study of three solar water heaters made of flat-plate collectors with different absorber configurations. The performance of the three solar water heaters is assessed under the same conditions. The collectors have the same surface area and are glazed. The theoretical model for each collector type, with the transient effects taken into account, is based on a control volume. By considering a small element of the collector in each case and the storage tank, six partial differential equations were developed for each solar water heater and were solved numerically for a cloudy day. This study shows that the thermal performance obtained with the solar water heater using the absorber-pipe lower bond configuration in the solar collector is always greater than the two others. These results showed that the solar water heater made of the absorber-pipe lower bond configuration is more efficient than the other systems.